2016
DOI: 10.1038/nature17438
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric catalytic formation of quaternary carbons by iminium ion trapping of radicals

Abstract: A central goal of modern organic chemistry is to develop novel catalytic enantioselective carbon-carbon bond-forming strategies for forging quaternary stereogenic centres. While considerable advances have been achieved in the realm of polar reactivity 1 , radical transformations have found very limited application 2 . This is despite the fact that open-shell intermediates are intrinsically primed for connecting structurally congested carbons, as their reactivity is only marginally affected by steric factors 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
159
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(173 citation statements)
references
References 31 publications
0
159
0
6
Order By: Relevance
“…While appealing from a synthetic standpoint, we recognized that the dioxolane methylene of substrate 2a served as a competitive site of activation by TBADT as demonstrated by Fagnoni and coworkers, 34 suggesting that the elimination of this group would increase the reaction efficiency. To our delight, subjecting phenyl dimethyl propanal 3a to the same conditions afforded two alkenes in a combined yield of 73%, and a higher selectivity of 6.3 : 1 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…While appealing from a synthetic standpoint, we recognized that the dioxolane methylene of substrate 2a served as a competitive site of activation by TBADT as demonstrated by Fagnoni and coworkers, 34 suggesting that the elimination of this group would increase the reaction efficiency. To our delight, subjecting phenyl dimethyl propanal 3a to the same conditions afforded two alkenes in a combined yield of 73%, and a higher selectivity of 6.3 : 1 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Elegant work from the Yoon and Melchiorre groups has subsequently demonstrated that by using a chiral Lewis acid or organocatalyst respectively, these transformations can be rendered asymmetric (vide infra). 33,34 …”
Section: Redox-neutral Amine α-Functionalizationmentioning
confidence: 99%
“…Recently, Melchiorre and co-workers were able to elegantly leverage the long-established LUMO lowering strategy of iminium catalysis to develop asymmetric conjugate additions of α-amino radicals, derived from N -arylamines, to α,β-unsaturated ketones (Scheme 9). 34 A key challenge in the development of radical conjugate additions to iminium ions is the propensity for the radical cation intermediates (such as 18) to undergo β-scission to regenerate the iminium species (i.e., 17 ). 48 To overcome this issue, chiral primary amine catalyst 20 was employed wherein rapid intramolecular electron transfer between the electron-rich carbazole and the α-iminyl radical cation functionality of 18 occurs, thereby delivering the corresponding enamine and precluding an undesirable β-scission event.…”
Section: Dual Photoredox Organocatalysis: Covalent Activation Modesmentioning
confidence: 99%
“…Their construction has long been recognized as an important challenge to the field of chemical synthesis, and several distinct catalytic, enantioselective approaches have been developed in response. 1,2,3,4 Notable examples include cycloadditions, 5 α and β-alkylation and arylation of carbonyls, 68 3,3′-additions, 9 S N 2′ reactions, 10 and Heck-type cross-couplings. 11 Each of these very powerful methods relies on enantiofacial addition across a prochiral substrate (Figure 1a) and therefore requires the preparation of stereochemically well-defined starting materials (such as trisubstituted olefins), and subsequent enantioselective bond formation.…”
mentioning
confidence: 99%